2012
DOI: 10.1111/j.1600-048x.2012.05527.x
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization, nestling growth and reproductive success in a moderately declining house sparrow population

Abstract: Ecological conditions are likely to change with increasing urbanization, influencing the demography and size of animal populations. Although one of the most tightly linked species to humans, the house sparrow has been suffering a significant decline worldwide, especially in European cities. Several factors have been proposed to explain this conspicuous loss of urban sparrows, but studies evaluating these factors are usually restricted to Britain where the decline was very drastic, and it is unclear whether sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
91
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 40 publications
6
91
1
Order By: Relevance
“…According to this, a study on chick-feeding behaviour of the same species provides direct evidence for the hypothesis that suburban nestlings receive diet of lower quality and/or quantity as their parents delivered significantly fewer large prey items e.g. large caterpillars or orthopterans than those in rural habitats (Seress 2014). These large prey items seem to be the most valuable type of nestling food since their delivery rate strongly predicts fledging mass and recruitment (Schwagmeyer & Mock 2008).…”
Section: Seress G and Liker Amentioning
confidence: 88%
See 1 more Smart Citation
“…According to this, a study on chick-feeding behaviour of the same species provides direct evidence for the hypothesis that suburban nestlings receive diet of lower quality and/or quantity as their parents delivered significantly fewer large prey items e.g. large caterpillars or orthopterans than those in rural habitats (Seress 2014). These large prey items seem to be the most valuable type of nestling food since their delivery rate strongly predicts fledging mass and recruitment (Schwagmeyer & Mock 2008).…”
Section: Seress G and Liker Amentioning
confidence: 88%
“…A recent study on House Sparrows also demonstrated increased nestling production in mealworm-supplemented nests, although this increase was similar in suburban and rural habitats (Peach et al 2014). The impacts of nestling diet were also supported by a study in which urban and rural house Seress et al 2012) sparrows were kept in aviaries supplied with ad libitum food of diverse composition: these birds performed similarly in all aspects of breeding parameters, despite the marked differences found between free-living suburban and rural populations of the same geographic region .…”
Section: Seress G and Liker Amentioning
confidence: 94%
“…Moreover, a large number of studies have also shown that urbanization affects reproductive performances, such as phenology or the number of young produced (Both et al, 2004;Chamberlain et al, 2009;Ausprey and Rodewald, 2011;Stracey and Robinson, 2012;Deviche and Davies, 2014;Møller et al, 2015). Surprisingly, the influence of urbanization on the phenotype and quality of developing offspring has been much less studied (Heiss et al, 2009;Seress et al, 2012;Salmón et al, 2016). Early developmental conditions are however crucial to study because they are known to have important long-term consequences on individual phenotypes and adult performances (survival and reproduction, Lindström, 1999;Metcalfe and Monaghan, 2001;Monaghan, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, urbanization often delays and impairs growth in bird species (Chamberlain et al, 2009;Heiss et al, 2009;Seress et al, 2012;Bailly et al, 2016). Similarly, urbanization is often associated with lower offspring productivity in wild vertebrates (Chamberlain et al, 2009;Bailly et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature, predator and parasite communities, artificial noise and light, availability and/or quality of resources, and pollution are among important features that contrast between cities and natural habitat (Collier, 2006;Evans et al, 2009b;Slabbekoorn, 2013). Cities are frequently described as resource-poor habitats for birds during the breeding season, and several works have shown that prey required for chicks are less abundant, smaller and poorer in key nutrients for growth and survival, such as carotenoids (Isaksson and Andersson, 2007;Seress et al, 2012). Those descriptive studies provided some data that allowed the design of experimental supplementation aimed at testing whether the quantity (energy intake) or the quality of resources (e.g., carotenoids) could explain the contrast of breeding performance between urban and non-urban populations (Peach et al, 2014;Giraudeau et al, 2015).…”
mentioning
confidence: 99%